Revisional notes on Siniphanerotomella He et al. (Hymenoptera Braconidae Cheloninae) with description of a new species from China - Yao, Junli; Achterberg, Cornelis Van; Zhao, Qingyan; Zhou, Jin-Jin; Peng, Yanqiong (Zootaxa, 2024)
Siniphanerotomella He, Chen et van Achterberg, 1994 is a genus endemic to China with three described species. A fourth new species from Yunnan (China), S. yunnanensis Yao et van Achterberg, sp. nov., is described and illustrated. In addition, S. disparclypeolus Ji et Chen and the female of S. fanjingshana He et al. are for the first time fully illustrated. Additional revisional notes on Siniphanerotomella are provided as is a key to all known species of this genus.